Application of botulinum toxin in maxillofacial field: Part III. Ancillary treatment for maxillofacial surgery and summary - Kyung-Hwan Kwon; Kyung Su Shin; Sung Hee Yeon; Dae Gun Kwon (SpringerOpen, 2019)
Abstract Botulinum toxin (BTX) has various therapeutic indications: bruxism, square jaw, facial wrinkle, oral ulcer and maxillofacial pain, etc. In this paper, we will discuss the effectiveness of using BTX in dental implant surgery and orthognathic and orthodontic treatment. We summarized the clinical application of botulinum toxin in the maxillofacial field at the finale.